Pendidikan Emosi dalam Perspektif Al-Quran dan Al-Hadits - Sumarno Sumarno (Proceedings of Annual Conference for Muslim Scholars, 2017)
Abstract: A person's ability in controlling his emotions showed that he was able to keep a confidence. It is also a mirror of one's maturity in being the face of any circumstance. In a review of the al-qur’an and the al-hadits of human emotion consists of several properties that look like; scared, sad, angry, resentful, jealous, envious, spiteful, arrogant remorse, shame, embarrassment, elation and love that can rub off on planned human nor instantly. In the perspective of the al-qur’an and al-haditsof urgency control emotion in psychology in man will have great significance and an Islamic human mental attitude in delivering human towards life that mature, balanced, harmonious independence. The Qur'an also hinted at psychological strife experienced by man, namely between the tendencies on the pleasure the pleasure of physical and tendencies on the temptationsthe temptations of earthly life, therefore need to be controlled his emotions. As for the effort in carrying out the education of the emotions is in a way; first; keep the oral, second; away from the "backbiting", third; avoid mutual hate, fourth; avoid the nature of the debate, fifth; leave the immoral deeds.Keywords: Emotional Education, Al-Quran And Al-Hadits